(3TQM GdegPHs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3Ydi Hf YHO GdQMef Hf Ydi GdbGYi (B/ (3TgGH GdOjf GdCPQYi s)
(3ChdgG (B:s
(3CeG HYO abO bGd Gddg GdYXje GdYRjR GdMcje (B: (3heG NdbJ GdLf hGdEfS EdG djYHOhf eG CQjO efge ef QRb heG CQjO Cf jWYehf s
(3BNQgG (B:s
(3bGd aEf bjd gdG hGddg CYde HGdUhGH BNQ GdeLdO GdChd ef GdeLehY ai TQM GdegPH s
(3GdfSNI HgG MhGTs
(3HgG ebGHdI Ydi jO CHh GdYHGS CMeO Hf eMeO Hf YHGS Hf CHj HcQ GdCfUGQi GdTGaYis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs